Na(+)/K(+)-pump ligands modulate gating of palytoxin-induced ion channels - Artigas, Pablo (The National Academy of Sciences, 2003)
The Na(+)/K(+) pump is a ubiquitous P-type ATPase that binds three cytoplasmic Na(+) ions deep within its core where they are temporarily occluded before being released to the extracellular surface. The 3Na(+)/2K(+)-exchange transport cycle is completed when two extracellular K(+) ions bind and become temporarily occluded within the protein and subsequently released to the cytoplasm. Coupling of Na(+)-ion occlusion to phosphorylation of the pump by ATP and of K(+)-ion occlusion to its dephosphorylation ensure the vectorial nature of net transport. The occluded-ion conformations, with binding sites inaccessible from either side, represent intermediate states in these alternating-access descriptions of transport. They afford protection against potentially catastrophic effects of inadvertently allowing simultaneous access from both membrane sides. The marine toxin, palytoxin, converts Na(+)/K(+) pumps into nonselective cation channels, possibly by disrupting the normal strict coupling between opening of one access pathway in the Na(+)/K(+) ATPase and closing of the other. We show here that gating of the channels in palytoxin-bound Na(+)/K(+) pumps in excised membrane patches is modulated by the pump's physiological ligands: cytoplasmic application of ATP promotes opening of the channels, and extracellular replacement of Na(+) ions by K(+) ions promotes closing of the channels. This suggests that, despite the presence of bound palytoxin, certain partial reactions of the normal Na(+)/K(+)-transport cycle persist and remain capable of effecting the conformational changes that control access to the pump's cation-binding sites. These findings affirm the alternating-access model of ion pumps and offer the possibility of examining ion occlusion/deocclusion reactions in single pump molecules.